Economic parameters of transportation by “Cold Express” trains on the example of the route Vladivostok—Moscow—St. Petersburg - S. P. Vakulenko; D. Yu. Romenskiy; M. I. Mekhedov; A. A. Gavrilenkov; A. M. Nasybullin; V. V. Solov'ev (Вестник Научно-исследовательского института железнодорожного транспорта)
Currently, a project for organizing the transportation of perishable freights by “Cold Express” trains is under development, which is a new transport product aimed at delivering food, agricultural raw materials and other highly profitable goods to cities where regular container trains are impractical. The article discusses the economic efficiency of the investment project for organizing the transportation of freights in regular refrigerated container trains on the example of the Vladivostok—Moscow—St. Petersburg route, taking into account the arrangement of at least 18 container sites capable of handling transit container trains. Transportation according to the “Cold Express” concept involves the delivery of freights on the Vladivostok— Moscow—St. Petersburg route to associated large cities by container train loaded with refrigerated and insulated containers, according to a developed schedule with a known arrival and departure time. Capacity of the freight transportation market on the pilot route of the “Cold Express” is 2.0 million tons with the development of transportation in both directions when reaching the design capacity. Freight traffic will be formed by 23 stops on the route, 2 port hubs, 2 border land crossings with a traffic size of 7 pairs of trains per week. As part of the project, an assessment was made of the need for the local reconstruction of passing stations and equipping them with new ones or refurbishing existing container terminals. At the same time, the commissioning of these terminals is supposed to be gradual within 7 years of the project, which also allows gradually increasing the freight base and improving the quality of transportation. The article presents the results of calculations of the commercial efficiency of the project for the Russian Railways as the owner of the infrastructure, carrier and operator of these container terminals, which show its high prospects. Even with an incomplete train load predicted due to uneven density of freight traffic, the net discounted payback period is 10 years.